Stability of ultra-high pressure treated freshly squeezed Hami melon juice under simulated commercial cold chain conditions - Jinxiao Cheng; Congcong Huai; Di Shen; Yining Xia; Yang Yang; Yifan Gu; Jiakai Yu; Lingling Pang; Jia Liu; Yanfang Pan (Food Control, 2026)

Carbon-efficient ride-pooling at intercity railway hubs: Nonlinear topological mechanisms and algorithmic insights - Zechao Ma; Tianqi Gu; Jiayan Zhang; Long Cheng; Inhi Kim; Bin Yu (Transportation Research Part D: Transport and Environment, 2026)

Modified β-glucans promote saponin and fucosylated chondroitin sulfate biosynthesis in sea cucumber Apostichopus japonicus in association with activation of the TLR-MAPK signaling pathway - Zezheng Qi; Zeyu Zhang; Wenyue Dai; Hongmei Ma; Junpeng Ge; Yutong Yu; Mengling Cheng; Wenjian Zhao; Shihui Pan; Min Gu; Nan Bai (Fish & Shellfish Immunology, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Dual-color switchable sensing platform based on dual-emission chiral carbon dots for specific and visual detection of cystatin C - Daohong Cheng; Wanqing Ni; Na Yu; Xinru Gu; Enqi Liu; Siyu Zhou; Tianyu Wei; Xingyi Ma; Guoying Sun; Yibing Liu (Chemical Engineering Journal, 2026)

Green synthesis of a histidine-copper biomimetic enzyme for sustainable degradation of sulfamethoxazole in aquaculture wastewater - Yini Zhao; Long Cheng; Tao Yu; Long Gu; Xiangyi Zhang; Hangfei Gao; Zhicen Liu; Ze Fan; Ting Yan; Dongli Qin; Xinyue Zhao; Haijiao Xie; et al. (Journal of Environmental Chemical Engineering, 2026)

Microplastics in China’s commercial crayfish (Procambarus clarkii): Tissue-specific characteristics and potential human health risks - Qingyuan Guo; Yu Zhang; Qingqin Meng; Ziyou Gu; Xiaomei Shen; Mingzhe Cai; Cheng Ding; Min Xu (Environmental Monitoring and Assessment, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Synergistic T cell and microbiome dysregulation in FOXP3-mediated immune enteritis: insights from multimodal omics - Meiling Jin; Cheng Jin; Shunlai Shang; Yuqing Gu; Peng Jin; Haibin Yu; Diangeng Li (Science China Life Sciences, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rapid behavioral regulations facilitate the formation of a novel migration route in swan geese - Zhongru Gu; Juan Long; Xinying Shi; Xin Liu; Zhuoran Kuang; Zhenyu Zhong; Jiade Bai; Zhibin Cheng; Nyambayar Batbayar; Batbayar Bold; Libo Zhou; Junfeng Chen; et al. (Science Bulletin, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Correction to: RP13 516M14.1 Regulates Autophagy Through miR 429 via Both a ceRNA Network and Direct Interaction - Zhijian Yang; Anyu Zeng; Baoxi Yu; Chao Xie; Weiwen Zhu; Hailong Liu; Cheng Gu; Ming Fu (Biochemical Genetics, 2026)

Promoter-driven enhancement of PHBV synthesis in recombinant Escherichia coli using glucose and propionate as carbon sources - Zhao-song Huang; Cheng-jiao Yu; Zi-miao Yan; Chang-feng Miao; Ling-yi Hou; Peng-fei Gu; Xiang-yu Fan; Qiang Li (Archives of Microbiology, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

In-Situ sulfur implantation efficiently promoting nitrogen removal in low-carbon anoxic-oxic systems - Jia-Min Xu; Miao Gu; Yi-Fan Zhang; Guodong Zhang; Jia-Qiang Lv; Yu-Qi Wang; Yao Chen; Guijiao Zhang; Daheng Ren; Xuchen Ba; Bin Gao; Hao-Yi Cheng (Water Research, 2026)

The Holocene hydroclimatic changes, palsa peatland development and vegetation history in the inner part of the Central Siberian Plateau (Russia) - Elena Yu. Novenko; Anatoly S. Prokushkin; Natalia G. Mazei; Elya P. Zazovskaya; Dmitry A. Kupriyanov; Anton E. Shatunov; Rodion A. Andreev; Ekaterina A. Makarova; Maria V. Kusilman; Alexander A. Komarov; Xiuyuan Gu; Andrey N. Tsyganov; et al. (Quaternary International, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Fabrication of acid-resistant nanofiltration membranes with intrinsic positive charges for lithium recovery - Yue Shen; Bingxin Gu; Xinhe Zhang; Yu Guo; Huiting Zhang; Cheng-Gang Jin; Bohao Chen; Yahua Lu; Gangqiang Yu; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

RP13-516M14.1 Regulates Autophagy Through miR-429 via Both a ceRNA Network and Direct Interaction - Zhijian Yang; Anyu Zeng; Baoxi Yu; Chao Xie; Weiwen Zhu; Hailong Liu; Cheng Gu; Ming Fu (Biochemical Genetics, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Synergistic photovoltaic cooling and water-resource recovery enabled by a composite evaporation gel - Yuqing Su; Yi Lu; Ruonan Gu; Wei Wu; Xuyu Yu; Shaoan Cheng (Desalination, 2026)

Association between Lipid Accumulation Product and 3-Month Functional Outcome after Ischemic Stroke: the Obesity-Stroke Paradox - Yuan Ren; Ying Zhou; Tian-yu Gu; Yang Cheng; Wei-hua Wu; Xiao-guang Dong; Feng-e Li; Yu-sheng Zhang (Translational Stroke Research, 2026)

Model-Dependent Attenuation of Seizures by Cinnabar - Yuang Gu; Yu Yao; Qiuwen Lou; Xinyan Zhu; Ju Lan; Chenshu Gao; Shuangshuang Wu; Jingjia Liang; Cenglin Xu; Yi Wang; Heming Cheng; Zhong Chen (Neuroscience Bulletin, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Analysis of Wave Height and Period in the Yangtze River Delta and Adjacent Waters Based on a 31-Year High-Resolution Wave Hindcast - Wenyun Guo; Jiepeng Gu; Tao Qin; Yu Zhang; Yi Zhou; Xinyi Shen; Cheng Li (Journal of Marine Science and Engineering, 2026)
This study presents a 31-year (1993–2023) wave hindcast using a high-resolution two-domain nested numerical wave model implemented with Simulating Waves Nearshore (SWAN). The spatiotemporal variability and long-term trends of two wave parameters (significant wave height Hs and spectral peak period Tpeak) are systematically analyzed for the Yangtze River Delta (YRD) and its adjacent waters. Validation against in situ buoy measurements confirms that the SWAN model effectively reproduces the regional wave conditions. Results indicate that mean wave conditions are primarily modulated by the Asian monsoon, whereas extreme wave events are predominantly influenced by typhoons. This leads to pronounced differences in spatial patterns and seasonal variability between mean and maximum Hs values. In addition, the regional interannual variations of Hs and Tpeak exhibit different degrees of correlation with the Niño 3.4 index, the Pacific Decadal Oscillation (PDO) index and the Western Pacific Subtropical High Ridge Position (WPSH) Index. Overall, both Hs and Tpeak exhibit positive trends over the study period, and both positive trends shift remarkably between seasons. The positive trends in mean wave conditions are mild during spring and summer but more pronounced in autumn and winter. Statistically significant increases in seasonal mean Hs are identified in parts of the East China Sea (0.35 cm a−1 in autumn) and the southern Yellow Sea (0.27 cm a−1 in winter). Notably, not all trends are positive: the 90th percentiles of both Hs and Tpeak during summer exhibit widespread declining trends, although they are not statistically significant.

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Dynamic prediction of carbon and nitrogen accumulation in winter wheat grain: Source-sink theory integrated with UAV multispectral imagery - Zehua Fan; Cuiping Liu; Fengyuan Yu; Yongliang Lai; Qiang Wang; Zhiyong Zhang; Juanjuan Zhang; Jinpeng Cheng; Xinming Ma; Xiaohe Gu; Shuping Xiong (Computers and Electronics in Agriculture, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Substrate-driven enrichment and mining of ligninolytic bacteria for efficient lignin-to-PHA conversion - Tao Xu; Chong Han; He Liu; Zi-Yi Zhao; Fan-Li Zeng; Yu-Cheng Gu; Zhi-Hua Liu; Bing-Zhi Li (Chemical Engineering Journal, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

Evaluation of quinazolin-4(3H)-one derivatives containing the bioactive acetohydrazide group as fungicidal candidates - Wenfei Zhang; Jiacheng Liu; Sifei Qi; Zihan Li; Yiwen Chen; Yufei Gong; Xiangkun Luo; Shuo Wang; Feng Liu; Yu-Cheng Gu; Xuewen Hua (Pesticide Biochemistry and Physiology, 2025)

Thermal decomposition characteristics, products, and thermal transformation mechanisms of fluorine-containing organic components in lithium-ion batteries - Hui Liu; Jingkun Han; Yuheng Feng; Chongqing Nong; Yu Liu; LeiLei Cheng; Jing Gu; Haoran Yuan (Journal of Environmental Chemical Engineering, 2025)

Harnessing visible light-activated humic acid and size-exclusion catalysis for efficient pollutant degradation in complex water system - Chenyong Liu; Xiufang Shen; Shaoqun Tao; Yu Liu; Zhonglin Chen; Weichuan Qiao; Cheng Gu; Ming Zhang (Journal of Environmental Chemical Engineering, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Butterfly-inspired ultraviolet vision chip based on ZnO memristor arrays for real-time dynamic plant motion tracking - Yang Liu; Junmeng Guo; Jiao Wang; Yuwei Zhao; Yatao Zhang; Guangxiang Gu; Haoran Ruan; Pengfei Li; Yu Sun; Luyao Zhang; Zuliang Du; Gang Cheng (Chemical Engineering Journal, 2025)

Injectable GelMA microsphere-integrated hyaluronic acid-polyphenol hydrogel system with multifunctional injury microenvironment modulation promotes peripheral nerve regeneration - Bo Ma; Hailin Ma; Baixin Gu; Kangling Xu; Pei Cao; Xiaotong Wu; Tiantian Qi; Rou Wen; Tianze Sun; Junyu Su; Hanwen Cheng; Yujie Wang; et al. (Carbohydrate Polymers, 2025)

New sesquiterpenoids from the flowers of pentanema britannicum (L.) D.Gut.Larr - Zhen Pei; Yan-Nan Ji; Xin-Yue Zhang; Yu-Qing Xie; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2025)

Galvanic effects between mackinawite and pyrogenic carbon: Enhancing radical-mediated ciprofloxacin transformation - Danning Lu; Longgang Chu; Haoran Yu; Zhaoyue Sun; Xiru Chen; Ruobing Wang; Xing Liu; Zhanghao Chen; Juan Gao; Cheng Gu (Journal of Hazardous Materials, 2025)

Control strategy to improve sustainable flux for a high-solid AnMBR in co-digesting food waste and sewage sludge - Hui Cheng; Kaiyi Gu; Yemei Li; Guangze Guo; Chang-Tang Chang; Wenshan Guo; Yu-You Li (Journal of Environmental Management, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Trash or treasure? Unlocking dark matter of enantiomeric natural products in innovative drugs discovery for potent angiogenesis inhibitors - Yan-Wei Wu; Xiao-Feng Mou; Zhong-Yuan Chen; Xiao-Jia Xue; Wen-Hui Wang; Jin-Zhou Guo; Bo-Qi Zhang; Ting-Ting Xue; Qun Zhang; Mei-Yan Wei; Yu-Cheng Gu; Gulab Said; et al. (Marine Life Science & Technology, 2025)
The occurrence and development of tumors rely on the nutritional supply from blood vessels, which also serve as the main pathway for tumor metastasis. Inhibiting angiogenesis is one of the main strategies for cancer treatments. Chiral drugs, encouraged and inspired by chiral natural products, make up a major portion of marketed drugs. However, as an important source for synthetic chemistry and drug discovery, the counterpart of chiral natural products, the enantiomers, has received little attention. Here, we constructed a compound library containing 100 racemates ( ±)- 1 – 100 and 4 pairs of enantiomers ( 33 , 48 , 59 , 68 ) of 3,4-dioxygenated-4-aryl-quinolin-2(1 H )-one alkaloids. Through extensive activity screening, we found that the compounds with 3 R , 4 R configuration, opposite to the natural products, exhibited potent angiogenesis inhibitory activity in zebrafish, while the 3 S , 4 S -configured natural derivatives have no effects. More importantly, compound ( +)- 48 , named as (3 R , 4 R )-CHNQD-00728, significantly inhibited hepatic tumor growth in doxycin hydrochloride-induced liver-specific enlargement zebrafish. Examining the phenomenon and unlocking dark matter of enantiomeric natural products in innovative drugs discovery can provide a new perspective on organic synthesis and medicinal chemistry, thus enabling a broader exploration.

Optimal location of free-floating bike-sharing dispatching hubs: A multi-scale perspective - Wendong Chen; Yu Gu; Xuewu Chen; Long Cheng; Jonas De Vos (Journal of Transport Geography, 2025)

Environmental concentrations of TCEP and TDCIPP induce dysbiosis of gut microbiotal and metabolism in the honeybee (Apis mellifera L.) - Tao Cang; Weijie Gu; Yu-Cheng Zhu; Mingcheng Guo; Lu Lv; Changxing Wu; Yuanxiang Jin; Yanhua Wang (Journal of Hazardous Materials, 2025)

Monitoring of aerosol optical-microphysical properties from DPC/GF-5(02): A case study of dust event in north China plain - Yujia Cao; Cheng Chen; Haixiao Yu; Xiaobing Sun; Xiao Liu; Haoran Gu; Yisong Xie; Jin Hong; Zhengqiang Li (Atmospheric Environment, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Electrocatalytic membrane-driven ozonation to reconstruct the extracellular polymeric substance for enhanced sludge dewatering - Yantao Song; Wei Zhang; Zhenao Gu; Yu Cheng; Haihua Bao; Jiaqi Wang; Ning Wang; Yuting Liu; Zongqiang Zhu; Chengzhi Hu (Journal of Water Process Engineering, 2025)

Soil emissions of HONO and other nitrogen-containing gases: Insights into microbial pathways and moisture effects - Peng Cheng; Baobin Han; Zhilin Tian; Zhen Liu; Wenda Yang; Jianwei Gu; Xiaofang Yu; Hongli Wang; Min Zhou (Atmospheric Pollution Research, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Highly efficient removal of per- and polyfluoroalkyl substances by extrusion-regenerated aminated polyurethane sponges - Xinhao Wang; Hanyang Chen; Wenran Wang; Xiufang Shen; Jiabao Wang; Sen Chen; Xueru Yu; Chew Tin Lee; Zhanghao Chen; Cheng Gu (Water Research, 2025)

Sesquiterpene lactones from Carpesium abrotanoides L. fruits: characterization and bioactivity profiling - Peng-Bo Tang; Xin-Yu Zhang; Chao Zhang; Jiayi Zhang; Shuohong Liu; Francoise Sauriol; Yu-Cheng Gu; Yu-Fang Wang; Chang-Hong Huo (Natural Product Research, 2025)

Dek570-1, a PPR-DYW protein, is required for maize seed and plant development via modulation of C-to-U RNA editing in mitochondria and chloroplasts - Wenjie Li; Mengsha Zhao; Baiyu Liu; Yecan Liu; Jiaying Deng; Yu Gu; Min Liu; Wen Cheng; Zhaohua Ding; Kunpeng Li (Planta, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Conditional Tnfaip6-Knockout in Inner Ear Hair Cells Does not Alter Auditory Function - Yue Qiu; Song Gao; Xiaoqiong Ding; Jie Lu; Xinya Ji; Wenli Hao; Siqi Cheng; Haolinag Du; Yajun Gu; Chenjie Yu; Cheng Cheng; Xia Gao (Neuroscience Bulletin, 2025)

Potentially harmful effects of micro-/nanoplastics on humans as well as protective actions of dietary natural products - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Dan-Dan Zhou; Si-Yu Huang; Si-Xia Wu; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan (Trends in Food Science & Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Microwaving plus enzymatic pretreatment of safflower seeds increases the phenolic content and oxidative stability of extracted oil - Zhi Qin; Yun-Long Chang; Zi-Cheng Yang; Wei Fan; Zi-Meng Chen; Ling-Biao Gu; Zhao Qin; Hua-Min Liu; Xin-Liang Zhu; Yu-Xiang Ma (Food Chemistry, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

High-efficient nanoemulsions separation by surface manipulation of sands - Yanzheng Ji; Zhikang Cheng; Yifan Zhuang; Chenxia Xie; Chunhui Liu; Wancheng Gu; Yage Xia; Weilin Deng; Wei Wang; Qiang Zhang; Xinquan Yu; Youfa Zhang (Journal of Hazardous Materials, 2025)

Vine tea kombucha ameliorates non-alcoholic fatty liver disease in high-fat diet fed mice via antioxidation, anti-inflammation and regulation of gut microbiota - Jin Cheng; Si-Yu Huang; Ruo-Gu Xiong; Si-Xia Wu; Zhi-Jun Yang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Hui-Lian Zhu; Hua-Bin Li (Food Bioscience, 2024)

Efficient separation of per- and polyfluoroalkyl substances (PFAS) from water by aminated polyacrylamide hydrogel foam - Yichen Xu; Xueru Yu; Xinhao Wang; Yiqian Song; Wenran Wang; Ming Zhang; Deyang Kong; Zhanghao Chen; Cheng Gu (Chemical Engineering Journal, 2024)

Tetraphenylborate enhanced enzymatic production of γ-cyclodextrin: System construction and its mechanism - Zihang Jiang; Yu Xiao; Zhengyao Xu; Zhengbiao Gu; Zhaofeng Li; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Carbohydrate Polymers, 2024)

Simple preparation of nitenpyram-intercalated clay nanosheets with reduced leaching risk and improved safety to insect pollinators - Chengshuai He; Jiao Liu; Jikang Cheng; Zhe Yu; Hui Zhang; Aiguo Gu; Song Yang; Yunhao Gao; Congfen Gao (Journal of Hazardous Materials, 2024)

Correction to: Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Photochemical Transformation of Ibuprofen and Chlorophene Induced by Dissolved Organic Matter - Na Mi; Liuqing Huang; Xinhao Wang; Xueru Yu; Zhenfeng Shi; Xuan Ni; Hanyang Chen; Yong Shang; Xiufang Shen; Cheng Gu; Zhanghao Chen (Bulletin of Environmental Contamination and Toxicology, 2024)

The vertical partitioning between denitrification and dissimilatory nitrate reduction to ammonium of coastal mangrove sediment microbiomes - Yijun Fan; Zhengyuan Zhou; Fei Liu; Lu Qian; Xiaoli Yu; Fangjuan Huang; Ruiwen Hu; Hualong Su; Hang Gu; Qingyun Yan; Zhili He; Cheng Wang (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Natural-inspired hierarchic double-Janus solar evaporator for stable clean water production from high-salinity emulsions - Zhen Yu; Ruonan Gu; Yuqing Su; Yihang Li; Guangli Liu; Shaoan Cheng (Journal of Hazardous Materials, 2024)

Hydroxysafflor Yellow A and Tenuigenin Exhibit Neuroprotection Effects Against Focal Cerebral Ischemia Via Differential Regulation of JAK2/STAT3 and SOCS3 Signaling Interaction - Lu Yu; Cheng Zhang; Lingling Gu; Hong Chen; Yan Huo; Shuyan Wang; Jie Tao; Chuan Xu; Qiujuan Zhang; Mingliang Ma; Jun Zhang (Molecular Neurobiology, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Sono-assembly of ellagic acid into nanostructures significantly enhances aqueous solubility and bioavailability - Wei Gu; Ruolin Kong; Shuyang Qi; Xuxi Cheng; Xuyi Cai; Ziyun Zhou; Shunan Zhang; Hongyu Zhao; Jinyun Song; Qinglian Hu; Huiwen Yu; Huangjin Tong; et al. (Food Chemistry, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Preparation and evaluation of liquorice (Glycyrrhiza uralensis) and ginger (Zingiber officinale) kombucha beverage based on antioxidant capacities, phenolic compounds and sensory qualities - Ruo-Gu Xiong; Dan-Dan Zhou; Jin Cheng; Si-Xia Wu; Adila Saimaiti; Si-Yu Huang; Qing Liu; Ao Shang; Hua-Bin Li; Sha Li (International Journal of Gastronomy and Food Science, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Segmentation of wheat scab fungus spores based on CRF_ResUNet++ - Dongyan Zhang; Wenhao Zhang; Tao Cheng; Yu Lei; Hongbo Qiao; Wei Guo; Xue Yang; Chunyan Gu (Computers and Electronics in Agriculture, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Intensified denitrification in a fluidized-bed reactor with suspended sulfur autotrophic microbial fillers - Zhenao Gu; Zheying Liu; Yu Cheng; Zongqiang Zhu; Jiayu Tian; Chengzhi Hu; Jiuhui Qu (Bioresource Technology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Altered connectivity in the cognitive control-related prefrontal cortex in Parkinson’s disease with rapid eye movement sleep behavior disorder - Jinjing Liu; Xiaoya Zou; Jinming Gu; Qian Yu; Zhaoying Dong; Hongzhou Zuo; Xiaocui Chen; Xinyi Du; Dezhi Zou; Yu Han; Juan Peng; Oumei Cheng (Brain Imaging and Behavior, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

Parallel paired electrolysis-enabled asymmetric catalysis: simultaneous synthesis of aldehydes/aryl bromides and chiral alcohols - Bing Sun; Zhen-Hua Wang; Yun-Zhao Wang; Yu-Cheng Gu; Cong Ma; Tian-Sheng Mei (Science Bulletin, 2023)

The vertically-stratified resistomes in mangrove sediments was driven by the bacterial diversity - Jiaxiong Zeng; Yu Pan; Ruiwen Hu; Fei Liu; Hang Gu; Jijuan Ding; Songfeng Liu; Shengwei Liu; Xueqin Yang; Yisheng Peng; Yun Tian; Qiang He; et al. (Journal of Hazardous Materials, 2023)

A three-dimensional folded multistage distillation device with enhanced air convection for efficient solar interface evaporation - Yihang Li; Shaoan Cheng; Beichen Jin; Zhen Yu; Ruonan Gu (Desalination, 2023)

Endowing V6O13/CeVO4 heterojunction with substantial improvements on zinc ion storage performance - Jingyun Cheng; Shuai Nan; Shuang Yu; Kaitao Liu; Huaiqiang Gu; Lei Tan; Zhulin Niu; Dan Li; Hongqiang Wang (Chemical Engineering Journal, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Abrupt warming of the equatorial intermediate Pacific during Heinrich Stadial 1 - Shuai Zhang; Tiegang Li; Zhoufei Yu; Fengming Chang; Sifan Gu; Zhifang Xiong; Heng Liu; Fang Qian; Junru Zhang; Xuhua Cheng; Baohua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Bioactive compounds and health benefits of pomegranate: An updated narrative review - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Yibin Feng; Ren-You Gan; Hua-Bin Li (Food Bioscience, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

Sluggish lithium isotopic response of continental intraplate basalts to recycled sedimentary carbonate - Yang-Yang Wang; Cheng-Long Yu; Dong-Bo Tan; He Sun; Hai-Ou Gu; Fengtai Tong; Li-Hui Chen; Yilin Xiao (Lithos, 2023)

Truncated glycoprotein E of varicella-zoster virus is an ideal immunogen for Escherichia coli-based vaccine design - Tingting Chen; Jie Sun; Sibo Zhang; Tingting Li; Liqin Liu; Wenhui Xue; Lizhi Zhou; Siting Liang; Zhili Yu; Qingbing Zheng; Hai Yu; Tong Cheng; et al. (Science China Life Sciences, 2023)

Stability analysis of gravity anchor foundation of layered argillaceous sandstone under dry-wet cycles - Jing-cheng Zheng; Wei Chen; Ke-ren Zheng; Yu-peng Gu; Fei Wang; Zhen Huang; Yun Li (Journal of Mountain Science, 2023)

Enhanced evaporation performance of solar interface evaporator by modifying the evaporation layer surface with hydrophobic fumed silica - Yihang Li; Shaoan Cheng; Zhen Yu; Ruonan Gu; Yangxi Li; Hua Chen (Journal of Cleaner Production, 2023)

Particle size of biochar significantly regulates the chemical speciation, transformation, and ecotoxicity of cadmium in biochar - Shiguo Gu; Wei Zhang; Fei Wang; Zhanhang Meng; Yu Cheng; Zexuan Geng; Fei Lian (Environmental Pollution, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

Enhancement mechanism of magnetite on the ball-milling destruction of perfluorooctane sulfonate by iron - Jun Hu; Yifan Qiu; Bing Gu; Nv Yao; Zimo Lou; Zhuowei Cheng; Xianzhao Zhang; Jianming Yu (Environmental Pollution, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Flow pattern transition and wave characteristics of impinging jet flow on a spinning disk reactor - Dongxiang Wang; Chengjun Gu; Cheng Sun; Xiang Ling; Hao Peng; Xinjun Yang; Fangyang Yuan; Jiyun Du; Wei Yu (Chemical Engineering Journal, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

High-Efficient Visible-Light Photocatalysis Performance and Light-Corrosion Resistance of Ag3PO4 Constructed by double-Z System Composites - Wenran Wang; Xueru Yu; Yutong Zhang; Liuqing Huang; Hongyi Wang; Cheng Gu; Zhanghao Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Xylomexicanins K-N: limonoids from the leaves and twigs of Xylocarpus granatum - Shao-Jing Li; Li-Kang Zhao; Jin-Jun Chen; Chun-Hua Zhou; Xin-Li Huang; Yi-Bing Wu; Françoise Sauriol; Yu-Cheng Gu; Hiromasa Kiyota (Natural Product Research, 2022)

Heterologous expression, refolding, and characterization of a calcium-independent phospholipase A1 from Streptomyces albidoflavus - Shi Cheng; Zitao Guo; Chaojuan Liang; Yi Shi; Peng Geng; Yu Xin; Zhenghua Gu; Liang Zhang (Systems Microbiology and Biomanufacturing, 2022)

Temporal dynamics of fine root production, mortality and turnover deviate across branch orders in a larch stand - Changfu Huo; Jiacun Gu; Lizhong Yu; Peng Wang; Weixin Cheng (Oecologia, 2022)

DeepStack-DTIs: Predicting Drug–Target Interactions Using LightGBM Feature Selection and Deep-Stacked Ensemble Classifier - Yan Zhang; Zhiwen Jiang; Cheng Chen; Qinqin Wei; Haiming Gu; Bin Yu (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Xidaosterols A and B, two new steroids with unusual α -keto-enol functionality from the South China Sea sponge Neopetrosia chaliniformis - Bao Chen; Yu-Cheng Gu; Nicole J. de Voogd; Chang-Yun Wang; Yue-Wei Guo (Natural Product Research, 2022)

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

Structure modification, antialgal, antiplasmodial, and toxic evaluations of a series of new marine-derived 14-membered resorcylic acid lactone derivatives - Wei-Feng Xu; Na-Na Wu; Yan-Wei Wu; Yue-Xuan Qi; Mei-Yan Wei; Laura M. Pineda; Michelle G. Ng; Carmenza Spadafora; Ji-Yong Zheng; Ling Lu; Chang-Yun Wang; Yu-Cheng Gu; et al. (Marine Life Science & Technology, 2022)
Marine natural products play critical roles in the chemical defense of many marine organisms and are essential, reputable sources of successful drug leads. Sixty-seven 14-membered resorcylic acid lactone derivatives 3 – 27 and 30 – 71 of the natural product zeaenol ( 1 ) isolated from the marine-derived fungus Cochliobolus lunatus were semisynthesized by chlorination, acylation, esterification, and acetalization in one to three steps. The structures of these new derivatives were established by HRESIMS and NMR techniques. All the compounds ( 1 – 71 ) were evaluated for their antialgal and antiplasmodial activities. Among them, 14 compounds displayed antifouling activities against adhesion of the fouling diatoms. In particular, 9 and 34 exhibited strong and selective inhibitory effects against the diatoms Navicula laevissima and Navicula exigua (EC 50 = 6.67 and 8.55 μmol/L), respectively, which were similar in efficacy to those of the positive control SeaNine 211 (EC 50 = 2.90 and 9.74 μmol/L). More importantly, 38 , 39 , and 69 – 71 showed potent antiplasmodial activities against Plasmodium falciparum with IC 50 values ranging from 3.54 to 9.72 μmol/L. Very interestingly, the five antiplasmodial derivatives displayed non-toxicity in the cytotoxicity assays and the zebrafish embryos model, thus, representing potential promising antiplasmodial drug agents. The preliminary structure–activity relationships indicated that biphenyl substituent at C-2, acetonide at positions C-5′ and C-6′, and tri- or tetra-substituted of acyl groups increased the antiplasmodial activity. Therefore, combining evaluation of chemical ecology with pharmacological models will be implemented as a systematic strategy, not only for environmentally friendly antifoulants but also for structurally novel drugs.

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

The intriguing chemistry and biology of sulfur-containing natural products from marine microorganisms (1987–2020) - Yang Hai; Mei-Yan Wei; Chang-Yun Wang; Yu-Cheng Gu; Chang-Lun Shao (Marine Life Science & Technology, 2021)
Natural products derived from marine microorganisms have received great attention as a potential resource of new compound entities for drug discovery. The unique marine environment brings us a large group of sulfur-containing natural products with abundant biological functionality including antitumor, antibiotic, anti-inflammatory and antiviral activities. We reviewed all the 484 sulfur-containing natural products (non-sulfated) isolated from marine microorganisms, of which 59.9% are thioethers, 29.8% are thiazole/thiazoline-containing compounds and 10.3% are sulfoxides, sulfones, thioesters and many others. A selection of 133 compounds was further discussed on their structure–activity relationships, mechanisms of action, biosynthesis, and druggability. This is the first systematic review on sulfur-containing natural products from marine microorganisms conducted from January 1987, when the first one was reported, to December 2020.

Effect of mangrove restoration on sediment properties and bacterial community - Xiao-Xia Ma; Zhao-Yu Jiang; Peng Wu; Yong-Fei Wang; Hao Cheng; You-Shao Wang; Ji-Dong Gu (Ecotoxicology, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Selection and optimum fertilization of Betula platyphylla hybrid clones for growth - Shuyuan Song; Siqi Cheng; Zhen Jia; Minghui Li; Jiabao Ji; Yifan Yang; Chu Wang; Chenrui Gu; Qibin Yu; Yuhui Weng; Guifeng Liu (Trees, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

The metabolic and immunological characteristics of pregnant women with COVID-19 and their neonates - Jingjiao Zhou; Yudie Wang; Juan Zhao; Lixing Gu; Cheng Yang; Jun Wang; Heng Zhang; Yu Tian; Hu Tuo; Dan Li; Min Wei; Bing He (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Characterization of a recombinant sucrose isomerase and its application to enzymatic production of isomaltulose - Feng Zhang; Feng Cheng; Dong-Xu Jia; Yue-Hao Gu; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2021)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Increased interregional functional connectivity of anterior insula is associated with improved smoking cessation outcome - Chao Wang; Zhujing Shen; Peiyu Huang; Wei Qian; Cheng Zhou; Kaicheng Li; Qingze Zeng; Xiao Luo; Quanquan Gu; Hualiang Yu; Yihong Yang; Minming Zhang (Brain Imaging and Behavior, 2020)

2,3,7,8-Tetrachlorodibenzo-p-dioxin-induced aryl hydrocarbon receptor activation enhanced the suppressive function of mesenchymal stem cells against splenocyte proliferation - Guorui Zhang; Xiaoming Li; Yi Cheng; Haiyang Yu; Wen Gu; Zhilei Cui; Xuejun Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

Cerebral perfusion alterations in type 2 diabetes and its relation to insulin resistance and cognitive dysfunction - Ying Cui; Xia Liang; Hong Gu; Yuzheng Hu; Zhen Zhao; Xiang-Yu Yang; Cheng Qian; Yihong Yang; Gao-Jun Teng (Brain Imaging and Behavior, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Penimethavone A, a flavone from a gorgonian-derived fungus Penicillium chrysogenum - Xue-Mei Hou; Chang-Yun Wang; Yu-Cheng Gu; Chang-Lun Shao (Natural Product Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Toll-Like Receptor 4 Deficiency Causes Reduced Exploratory Behavior in Mice Under Approach-Avoidance Conflict - Chunlu Li; Yixiu Yan; Jingjing Cheng; Gang Xiao; Jueqing Gu; Luqi Zhang; Siyu Yuan; Junlu Wang; Yi Shen; Yu-Dong Zhou (Neuroscience Bulletin, 2016)

Extracting urban areas in China using DMSP/OLS nighttime light data integrated with biophysical composition information - Yang Cheng; Limin Zhao; Wei Wan; Lingling Li; Tao Yu; Xingfa Gu (Journal of Geographical Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

The spatial–temporal variations in optical properties of atmosphere aerosols derived from AERONET dataset over China - H. Chen; X. Gu; T. Cheng; Z. Li; T. Yu (Meteorology and Atmospheric Physics, 2013)

Atmospheric scattering and turbulence modulation transfer function for CCD cameras on CBERS-02b and HJ-1A/1B - Xiaoying Li; Xingfa Gu; Tao Yu; Tianhai Cheng; Jiaguo Li; Hailiang Gao; Zuo Wang (International Journal of Remote Sensing, 2012)

Initial research on the polarized reflectance of typical urban surface types measured by the Directional Polarimetric Camera - DongHai Xie; XingFa Gu; TianHai Cheng; Tao Yu; ZhengQiang Li; XingFeng Chen; Hao Chen; Jing Guo (Science China Earth Sciences, 2011)

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Saturation and comparative mapping of the genomic region harboring Hessian fly resistance gene H26 in wheat - Guo Tai Yu; Xiwen Cai; Marion O. Harris; Yong Qiang Gu; Ming-Cheng Luo; Steven S. Xu (Theoretical and Applied Genetics, 2009)

Morphology, ecology, and contaminant removal efficiency of eight wetland plants with differing root systems - Xiu-Yun Cheng; Wen-Yin Chen; Bin-He Gu; Xu-Cheng Liu; Fang Chen; Zhang-He Chen; Xian-Ye Zhou; Yu-Xiang Li; Hua Huang; Yun-Jin Chen (Hydrobiologia, 2009)

ROLLED LEAF 9, encoding a GARP protein, regulates the leaf abaxial cell fate in rice - Song Yan; Chang-Jie Yan; Xiu-Hong Zeng; Ya-Chun Yang; Yu-Wei Fang; Chun-Yan Tian; Ya-Wei Sun; Zhu-Kuan Cheng; Ming-Hong Gu (Plant Molecular Biology, 2008)

Diversity of centromeric repeats in two closely related wild rice species, Oryza officinalis and Oryza rhizomatis - Weidong Bao; Wenli Zhang; Qiuying Yang; Yu Zhang; Bin Han; Minghong Gu; Yongbiao Xue; Zhukuan Cheng (Molecular Genetics and Genomics, 2006)

B chromosome in a rice aneuploid variation - Z. K. Cheng; H. X. Yu; H. H. Yan; M. H. Gu; L. H. Zhu (Theoretical and Applied Genetics, 2000)